Pengaruh Penggunaan Media Poster Angka Terhadap Kemampuan Mengenal Angka Permulaan Pada Anak Usia Dini 4-5 Tahun di Tkq An-Namlu Palumbonsari Karawang - Syifa Fauziah; Astuti Darmiyanti; Feronica Eka Putri (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine whether the number poster learning media at TKQ An-Namlu Palubonsari Karawang has an impact on the ability of early childhood to recognize early numbers. At TKQ An-Namlu Palumbonsari Karawang, this study used experimental research and a one group pretest-posttest design with a sample of 10 children in group A. The research findings show that the use of poster media has an impact on people's ability to detect initial numbers. that the mean score on the pretest, SESA, was 33.50, and the average score on the posttest, 61. In addition, as seen from the findings of the paired sample T-test table, the calculated T-score was 38,439 with sig. (0.000), then the data can guarantee that the use of poster media greatly affects the ability of children aged 4 to 5 years to recognize basic numbers.